Real‐life evidence in evaluating effectiveness of treatment in Haemophilia A with a recombinant FVIII concentrate: A non‐interventional study in emerging countries. (4th February 2015) - Gouider, E.; Rauchensteiner, S.; Andreeva, T.; Al Zoebie, A.; Mehadzic, S.; Nefyodova, L.; Brunn, M.; Tueckmantel, C.; Meddeb, B.
Summary Some progress has been made regarding availability of recombinant factor VIII concentrates and prophylaxis for haemophilia A in emerging countries, where plasma‐derived concentrates were used in the vast majority. Clinical studies to document their introduction and effectiveness are so far not widely available in literature. This non‐interventional study evaluates the real‐life effectiveness and safety of prophylactic and on‐demand treatment with recombinant factor VIII formulated with sucrose (rFVIII‐FS) for bleed control and preservation of joints in emerging countries from Eastern Europe, North Africa and Middle East area. One hundred and eighty‐six patients from 11 countries were enrolled, mean ± SD age 12.8 ± 12.7 years. At enrolment, majority (79.6%) had severe haemophilia A (<2% IU mL−1), 47.8% had a target joint, 15% had an inhibitor history and one patient was on immune tolerance induction. During the 24‐month observation period, 58.1% of the patients were prescribed prophylaxis at every visit, 31.7% were on an on‐demand regimen. Patients with severe haemophilia A on prophylaxis (n = 82) had a mean annual rate of treated bleeds of 2.8 ± 4.4, whereas it was 19.1 ± 32.0 for the on‐demand group (n = 31), and a mean total Gilbert Score of 9.9 ± 10.3 at baseline and 4.1 ± 6.7 at study end; vs. 15.2 ± 17.3 and 13.7 ± 17.1 for on‐demand respectively. The majority of the bleeds (91.1%) were treated with one or two infusions. Four patients without inhibitor history had a first positive inhibitor test during the study. This study demonstrates the effective use of rFVIII‐FS in emerging countries and adds to the established safety profile of rFVIII‐FS.